Parametric Study on Shear Performance for Steel Fiber Reinforced Concrete Beams. Issue 7 (July 2015) - Seo, Junwon; Lee, Jaeha; Lopez, Maria M.
Many research studies into Fiber Reinforced Concrete (FRC) have shown the various advantages of using FRC. Accordingly, FRC has become widely used by engineering and construction companies as a non-structural strengthening component such as pavements and slabs on grade. Structural use of FRC such as a replacement of stirrups, however, has not received a similar acceptance rate in spite of the large research effort conducted in the past 50 years. The variability in the structural properties of FRC also makes FRC especially hard to standardize. In this study, fibers for use as a structural component of reinforced concrete elements were studied and verified. Stress-crack opening curves were obtained by inverse analysis and are used effectively for the prediction of the shear strength of FRC. A model developed using modified compression field theory (Vecchio and Collins 1986) was verified against recently obtained experimental data (Hockenberry and Lopez 2012) and found to match well. It was found that the fibers reduce the size effect. However, the size effects were not eliminated, but diminished due to the effect of the fibers in the reinforced concrete beams. Furthermore, a combination of the effects of fibers and stirrups was examined. It was found that fibers could be right alternatives to the shear stirrups in RC beams. Furthermore, propose empirical equations based on analysis and experimental results from other studies predicted shear strengths of FRC beam accurately.